2007
DOI: 10.1200/jco.2006.09.7758
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Laparoscopic-Assisted Resection of Colorectal Carcinoma: 3-Year Results of the UK MRC CLASICC Trial Group

Abstract: Successful laparoscopic-assisted surgery for colon cancer is as effective as open surgery in terms of oncological outcomes and preservation of QoL. Long-term outcomes for patients with rectal cancer were similar in those undergoing abdominoperineal resection and AR, and support the continued use of laparoscopic surgery in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
854
5
62

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,412 publications
(986 citation statements)
references
References 21 publications
46
854
5
62
Order By: Relevance
“…3 The robotic surgery is especially suited for dissection in pelvis which requires precise movements and fine tissue dissection near critical structures None of the patients in our study was CRM positive. A recent report from a multi-institutional study (CLASICC trial) comparing CRM results from laparoscopic colorectal cancer surgery vs open surgery showed a concern of higher positive rate in the laparoscopic arm [17,18]. One of the most important factors relating to adequacy of rectal excision is the mesorectal grade, which is related to oncological outcome [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The robotic surgery is especially suited for dissection in pelvis which requires precise movements and fine tissue dissection near critical structures None of the patients in our study was CRM positive. A recent report from a multi-institutional study (CLASICC trial) comparing CRM results from laparoscopic colorectal cancer surgery vs open surgery showed a concern of higher positive rate in the laparoscopic arm [17,18]. One of the most important factors relating to adequacy of rectal excision is the mesorectal grade, which is related to oncological outcome [2].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations of laparoscopic colorectal resection for the treatment of cancer have revealed superior short-term operative outcomes and noninferior oncologic outcomes compared with open surgery, the classic standard treatment [18,23,24]. Although laparoscopic colon surgery is very popular, there is little doubt that laparoscopic rectal surgery is technically very challenging and the learning curve for this procedure is longer and more demanding than for laparoscopic colectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the follow‐up duration was relatively short. Although we thought that LR would generally be identified within 3 years after surgery35, 36, 37 and some RCT were also designed to compare the OS, DFS, or LR at this time point,6, 38, 39 longer follow up is required to confirm these results. We plan to follow up this cohort until 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One of the principal difficulties of the laparoscopic approach is the limited space in the pelvis in which to operate, particularly in the male and with low-lying rectal tumours. Several case series and trials have demonstrated the safety and feasibility of the laparoscopic approach for rectal cancer [55][56][57][58][59][60][61][62][63]. These trials suggest that laparoscopic surgery affords similar oncological results to open surgery with less blood loss, have shorter recovery periods but take longer to perform.…”
Section: Management Of Early Rectal Cancer and The Malignant Polypmentioning
confidence: 99%